Quality assurance in the secretarial profession: its role in nation building - Sylvester, Ehidiamhen (Journal of Professional Secretaries and Office Administrators, 2013)
Secretarial profession is a career with technical skill that helps to achieve standard when procedures are properly followed. The purpose to this paper is therefore, to highlight the Quality Assurance in the Secretarial Profession, its role in nation building. To achieve this, the secretarial profession needs to follow surgical process to arrive at it destination. This process is a means of re-branding the secretarial profession to meet this standard it requires like other professional bodies such as law, engineer, nursing etc.